Adolescents' dramatic engagement predicts their in-session productive behaviors: A psychodrama change process study. (September 2017) - Orkibi, Hod; Azoulay, Bracha; Regev, Dafna; Snir, Sharon
Highlights: Psychodrama change process study with adolescents at-risk. Client dramatic engagement (DE) significantly linked with therapist bonding. Greater client DE increased the odds for client in-session productive behaviors. Greater client DE decreased the odds for client resistance in sessions. Abstract: This psychodrama change process pilot study examined the association between client in-session dramatic engagement, client in-session behaviors, and the client-therapist therapeutic bond. Sixteen Israeli adolescents at-risk (aged 13–16) received psychodrama group therapy in schools. The findings suggest that over the course of therapy, both in-session client dramatic engagement and general client involvement increased significantly. Client dramatic engagement significantly correlated with therapist-reported bonding with the client, but not with client-reported bonding with the therapist. Greater client dramatic engagement increased the likelihood for client in-session productive behaviors (cognitive-behavioral exploration, emotional exploration, insight, and therapeutic change) and decreased the likelihood for client resistance in sessions. The results highlight the possible relationships between change process variables that are understudied in the psychodrama and drama therapy literature. After reviewing the key factors that may increase resistance in adolescents, as well as therapist bonding and engagement strategies, the study limitations and future directions are discussed.